Characterizing artefact in the normal human 24-hour RR time series to aid identification and artificial replication of circadian variations in human beat to beat heart rate using a simple threshold - Clifford, G; McSharry, P; Tarassenko, L (2002)
The authors present an investigation into the incidences of ectopy and artefact as a function of time of day, heart rate and state changes for 19 normal subjects. State changes are defined to be a statistically significant change in mean or variance over a window of a few minutes. Artefact incidence is shown to be significantly correlated with state change and heart rate in normal humans, whereas ectopy exhibits no significant relationship. Artefact is therefore shown to be a source of information which can aid identification of activity or state changes and facilitate abnormality detection in patient populations. Timing thresholds are proposed which differentiate between artefact, ectopy and sinus beats. A classification system based upon the frequency of artefact occurrences in relation to state changes is presented which correctly separates 78% of the the real (normal) and artificial RR interval time series in event 2 of the CinC Challenge 2002 (entry number 38).